Suppression of electron-transfer characteristics of ferrocene by OTS monolayer on a silicon/electrolyte interface - Kulkarni, S. A.; Kakade, Bhalchandra A.; Mulla, Imtiaz S.; Pillai, V. K. (Journal of Colloid and Interface Science, 2006)
The passivating behavior of self-assembled monolayers (SAMs) of octadecyltrichlorosilane (OTS) on an n-type Si(100) electrode with and without a redox species like ferrocene in a polar non-aqueous medium has been investigated using techniques like contact angle measurements, Fourier transform infrared (FTIR) spectroscopy and X-ray photoelectron spectroscopy (XPS) to understand the role of the monolayer. The electron-transfer behavior of ferrocene is found to be drastically affected by the presence of monolayer and the reasons for these are analyzed as a function of the change in resistance, dielectric thickness and coverage of the monolayer. Electrochemical impedance analysis in the presence of ferrocene gives the monolayer coverage as 0.998 and the apparent rate constant calculated from this gives 4.85 x 10(-12) cm s(-1) in comparison with 4.4 x 10(-8) cm s(-1) for a similar electrode without any monolayer. A positive shift of 200 mV in the flat-band potential after monolayer formation also suggests the covalent coupling of the silane nionolayer offering a protective barrier. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: cyclic voltammetry; ferrocene; impedance analysis; octadecyltrichlorosilane (OTS); rate constant; self-assembled monolayer (SAM)

Reaction engineering for continuous production of silver nanoparticles - Deshpande, Javdeep B.; Kulkarni, Amol A. (Chemical Engineering & Technology, 2018)
A scalable process for the production of silver nanoparticles that allows for complete conversion of the limiting reactant is analyzed in detail. The kinetics of silver nanoparticle synthesis using citrate reduction are investigated and used for development of a reaction engineering model to facilitate the reactor design. The effect of temperature, pH, concentration and mixing (axial dispersion) on the rates of nucleation and growth are analyzed quantitatively. An approach that considers reaction kinetics coupled with quality of dispersion is developed for reactor design as well as selection of reactor configurations for the synthesis of specific particle sizes. The developed approach has been applied for continuous production of 10-L suspension silver nanoparticles with very narrow particle size distribution.
Keywords: kinetics; particle size distribution; rate constant; Reactor design; Silver nanoparticle production